THE ROLE OF LEADERSHIP IN INNOVATION PERFORMANCE: TRANSACTIONAL VERSUS TRANSFORMATIONAL STYLE - Dewiana Novitasari; Nana Supiana; Heri Supriatna; Muhamad Agung Ali Fikri; Masduki Asbari (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2021)
Abstract: The purpose of this study was to examine the effect of transactional and transformational on the innovation performance of lecturers. The population of this research is all lecturers at a private university in Tangerang totaling 180 people. The research sample used a random sampling method. The data used are primary data collected through a questionnaire. The number of returned and valid questionnaires was 120 samples. The data is processed using Structural Equating Model (SEM). The results of the study conclude that transactional and transformational leadership have a positive impact on the innovation performance of lecturers. This study proposes a model to improve the performance of lecturers in Tangerang through improving leadership practices in universities. This study can pave the way to improve the readiness of lecturers in facing the 4.0 education era. Abstrak: Tujuan penelitian ini adalah untuk menguji pengaruh transaksional dan transformasional terhadap kinerja inovasi dosen. Populasi penelitian ini adalah seluruh dosen pada salah satu universitas swasta di Tangerang berjumlah 180 orang. Sampel penelitian menggunakan random sampling method. Data yang digunakan adalah data primer yang dikumpulkan melalui kuesioner. Jumlah kuesioner yang kembali dan valid sebanyak 120 sampel. Data diolah dengan menggunakan Structural Equating Model (SEM). Hasil penelitian menyimpulkan bahwa kepemimpinan transaksional dan transformasional berpengaruh positif terhadap kinerja inovasi dosen. Penelitian ini mengusulkan model untuk meningkatkan kinerja dosen di Tangerang melalui peningkatan praktik kepemimpinan di perguruan tinggi. Kajian ini dapat membuka jalan untuk meningkatkan kesiapan dosen dalam menghadapi era pendidikan 4.0.